Recrystallization–precipitation interaction of a Ti microalloyed steel with controlled rolling process. (November 2020) - Chen, Songjun; Li, Liejun; Xia, Jinian; Peng, Zhengwu; Gao, Jixiang; Sun, Haibo
Abstract: The interaction between austenite static recrystallization and strain induced precipitation of a Ti microalloyed steel deformed in the non-recrystallization region was investigated by two-stage interrupted compression method and transmission electron microscopy (TEM). The softening rate curves of austenite were obtained by the true stress-strain curves of the two-pass of deformation. Results showed that the softening rates increased with increasing deformation temperatures. The softening rate curve exhibited a "S" shaped, and the static recrystallization was completed in 300 s when deformed at 1000°C, while deformed temperatures were lower than 950°C, the softening rates dropped sharply and increased very slowly as pass inter time increased. At 975°C or below, platforms appeared in softening curves, which implied strain-induced precipitates occurred during the isothermal process after the first deformation. The shortest incubation time of strain-induced precipitates was about 78 s when deformed at 925°C. Based on TEM results, strain-induced precipitates were found to be mainly distributed at dislocations and the diameters of the particles precipitated at dislocations were obviously larger than those of precipitated in other nucleation sites due to the effective route for the diffusion of Ti element. Evolution of austenite grains morphologies showed that the static recrystallization of deformed austenite was strongly inhibited by strain-induced precipitation and occurred again after the strain-induced precipitation finished.